Impacto del aumento del IVA en el costo de la canasta básica en la ciudad de Riobamba durante el año 2024. - Freire Saigua, Lisbeth Stefanny (2025)
This research paper analyzes the impact of the increase in the Value Added Tax (VAT) from 12% to 15%, implemented in Ecuador as of April 1, 2024, on the cost of products that make up the basic food basket in the city of Riobamba. The government's decision to increase VAT, aimed at strengthening tax collection in the face of the national economic and social crisis, generated direct effects on the economy of households, especially those with lower incomes. The study was developed under a mixed approach, combining quantitative and qualitative methods under a non-experimental design. Information was collected through surveys directed to a sample of 254 taxpayers from five urban parishes of Riobamba, selected through stratified sampling. The analysis of the results showed a significant increase in the prices of food and essential products, as well as changes in family consumption habits, such as a reduction in the purchase of certain goods and the substitution of cheaper alternatives. The research concludes that the VAT increase has reduced the purchasing power of Riobamba households, deepened economic inequalities and limiting access to basic necessities. It recommends implementing compensatory public policies, such as local support programs, to mitigate negative effects on vulnerable sectors. It is recommended to implement compensatory public policies, such as creating local support programs targeted at the most vulnerable sectors, to mitigate the negative effects of the fiscal adjustment and ensure more equitable conditions for these populations.